The contribution of ICT in improving the quality of education: a case of Higherlife Foundation, Masvingo. - Muzhingi, Nyasha Daphne (Midlands State University, 2017)
The research investigates if the project of Higherlife Foundation that it rolled out is benefiting and helping in transforming the quality of education that has been in shambles ever since the beginning of the economic meltdown. It focuses on the primary and secondary education in the province of Masvingo, in the rural parts of the province were the learning hubs have been placed. I investigated the role of ICT in the education sector and brought out the indicators of quality education that are being positively and negatively affected by the introduction of this global phenomenon of ICT in schools. The first chapter brings out how the education sector was before the introduction of ICT and seeks to bring out how transformation was greatly needed in the industry of education. Second chapter of the study investigated the role being played by ICT in improving the quality of education in the rural areas were HLF introduced learning hubs. In this chapter indicators of quality of education were highlighted in detail, showing that ICT is bringing a good change in the education sector as pass rates are changing, pedagogy is improving among other indicators of quality education. Chapter three is were the recommendations on how to improve the ICT projects and also what can be done to make ICT the ultimate solution for quality of education in Zimbabwe as a whole. Statistics in the research were taken from online sources and most of them were provided from the Higherlife Foundation group in Masvingo and also interviews and questionnaires were administered during the course of the research.